A Toxin-Antitoxin Module of Salmonella Promotes Virulence in Mice - De la Cruz, Miguel A.; Zhao, Weidong; Farenc, Carine; Gimenez, Grégory; Raoult, Didier; Cambillau, Christian; Gorvel, Jean-Pierre; Méresse, Stéphane (PLoS pathogens, 2013)
Toxin-antitoxin (TA) modules are widely prevalent in both bacteria and archaea. Originally described as stabilizing elements of plasmids, TA modules are also widespread on bacterial chromosomes. These modules promote bacterial persistence in response to specific environmental stresses. So far, the possibility that TA modules could be involved in bacterial virulence has been largely neglected, but recent comparative genomic studies have shown that the presence of TA modules is significantly associated with the pathogenicity of bacteria. Using Salmonella as a model, we investigated whether TA modules help bacteria to overcome the stress conditions encountered during colonization, thereby supporting virulence in the host. By bioinformatics analyses, we found that the genome of the pathogenic bacterium Salmonella Typhimurium encodes at least 11 type II TA modules. Several of these are conserved in other pathogenic strains but absent from non-pathogenic species indicating that certain TA modules might play a role in Salmonella pathogenicity. We show that one TA module, hereafter referred to as sehAB, plays a transient role in virulence in perorally inoculated mice. The use of a transcriptional reporter demonstrated that bacteria in which sehAB is strongly activated are predominantly localized in the mesenteric lymph nodes. In addition, sehAB was shown to be important for the survival of Salmonella in these peripheral lymphoid organs. These data indicate that the transient activation of a type II TA module can bring a selective advantage favouring virulence and demonstrate that TA modules are engaged in Salmonella pathogenesis.